Realization of the rule of law principle in the administrative procedure - Olexsandrivna Kolomoiets, Tetiana; Shkliar, Sergii; Viktorivna Hryshyna, Natalia; Leonidovich Borko, Andriy; Mykhailivna Kolotilova, Tetiana (DIXI, 2023)
The rule of law is a fundamental principle of law that is essential for the realization of administrative procedures, in particular in the spirit of a democratic and law-governed state defined by law, and in order to ensure the rule of law and the law, as well as the state’s obligation to ensure and protect the rights, freedoms or legitimate interests of a person and citizen. The principles of administrative procedure apply to administrative activities of administrative bodies that do not require the adoption of administrative acts. In this context, it is important to remember that an administrative body in conducting administrative proceedings is guided by the rule of law, according to which a person, his or her rights and freedoms are recognized as the highest values and determine the content and direction of the state’s activities. In addition, a very important aspect is that an administrative body carries out administrative proceedings exclusively on the basis, within the limits of its powers and in the manner provided for by national legislation, as well as on the basis of ratified international treaties. Given the importance of these aspects, the article explains such concepts as “administrative procedure” and “the rule of law principle”. The authors consider the realization of the rule of law principle in administrative procedures in the unity of three conditions: ensuring digital adaptability; ensuring clarity.